1999
DOI: 10.1136/mp.52.3.131
|View full text |Cite
|
Sign up to set email alerts
|

Association of p53 genomic instability with the glutathione S- transferase null genotype in gastric cancer in the Portuguese population

Abstract: This study does not support the hypothesis of an association between LOH in the p53 gene and the GSTM1 null genotype, but suggests that the GSTM1 null genotype might influence p53 genomic instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Of special interest is phase I CYP and phase II GSTs whose polymorphisms are related to substantial interindividual variation in metabolizing carcinogens and cancer risks [9]. Despite the biological plausibility for the role of these metabolizing enzymes in the etiology of GC, there have been a relatively small number of epidemiological studies which have evaluated these polymorphisms [16,17,18,19,20,21,22,23,24]. Previous studies in this field are summarized in Table 4.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Of special interest is phase I CYP and phase II GSTs whose polymorphisms are related to substantial interindividual variation in metabolizing carcinogens and cancer risks [9]. Despite the biological plausibility for the role of these metabolizing enzymes in the etiology of GC, there have been a relatively small number of epidemiological studies which have evaluated these polymorphisms [16,17,18,19,20,21,22,23,24]. Previous studies in this field are summarized in Table 4.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, GSTT1 and GSTM1 are involved in detoxifying a number of carcinogens, including those present in tobacco smoke. Few studies have evaluated the relationship between CYP2E1, GSTT1, and GSTM1 genetic polymorphisms and risk of GC, and the results have been conflicting [16,17,18,19,20,21,22,23,24]. Since interindividual and interethnic differences have been reported for these host susceptibility factors, the results of genetic polymorphism in different racial groups vary widely [25].…”
Section: Study Subjectsmentioning
confidence: 99%
“…In the multi-step carcinogenesis of the stomach, chronic gastritis preceded the formation of gastric cancer, and a great proportion of the clinical tumors occurred in connection with advanced forms of this pathology [57] . H pylori has been reported to be a Class I human carcinogen [58] , and chronic H pylori infection was shown to increase the risk for gastric carcinoma from 2.8 to 9 fold [59][60][61][62][63][64] . Ng et al [27] observed that the absence of the GSTM1 enzyme might increase the risk of developing gastric cancer in patients with H pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…The GSTM1 gene acts during phase II of xenobiotics metabolism and its correspondent enzyme plays an important role in detoxifying chemical compounds, including polyaromatic hydrocarbons, such as those found in cigarettes, foods, pollutants, agrochemicals, chemotherapeutic drugs and oxidative stress products (Conde et al 1999;Hirvonen 1995;London et al 1995;Zhong et al 1993b). Brazil is a large and highly heterogeneous country in regard to population, and differences in genic frequencies for control populations are easily found in different regions.…”
Section: Discussionmentioning
confidence: 99%